EDITORIAL NOTE Vol.63, n.2 GeoPantanal (8/2025) RA’E GA – THE GEOGRAPHIC SPACE IN ANALYSIS ISSN 2177-2738 (Online) - Galvanin , Edinéia Aparecida dos Santos; Silva, Joao dos Santos Vila da; Breunig, Fábio Marcelo (Ra’e Ga: o Espaço Geográfico em Análise, 2025)
This special issue of the RA’E GA - The Geographic Space in Analysis journal brings together 15 works selected from those presented at the 8th GeoPantanal, held from November 11 to 13, 2024, in the locality of Porto Cercado (Hotel SESC Pantanal), municipality of Poconé, MT, Brazil. The event seeks to encourage the production and dissemination of scientific knowledge about the Pantanal region, providing an exchange between researchers and the updating of geotechnology tools to the academic community and the public. The works were selected by a scientific committee composed of five PhD professionals representing the institutions UNESP, UFRJ, UFF, IBGE, and UFMT, belonging to the technical-scientific committee of the 8th GeoPantanal, and were again evaluated by a double-blind review process, attempting to meet the editorial standards of the Journal. It should be noted that the journal is currently classified with Qualis A1 by CAPES rank. The event was organized by Embrapa Agricultural Informatics, the Brazilian National Institute for Space Research, the State University of Mato Grosso, the São Paulo State University, and the Federal University of Mato Grosso. With this publication, the organizers of the event, with the support of the journal RA’E GA - The Geographic Space in Analysis, continue the dissemination of studies of the Pantanal and surrounding region, delimited by the Upper Paraguay Basin - BAP, contemplating the use of spatialized and georeferenced information in multi- and interdisciplinary studies. We take this opportunity to express our thanks to all those who contribute to the journal RA’EGA - The Geographic Space under Analysis, especially to the Reviewers and the Support Program for Periodical Scientific Publications of UFPR, who carried out the review of scientific and linguistic merit, respectively, fundamental activities for the quality of this special issue.